Acute liver failure in dengue haemorrhagic fever. (24th May 2015) - Arora, Shalabh; Nathaniel, Samson Devakiruba; Paul, Joseph Chacko; Hansdak, Samuel George
Abstract : While dengue virus infection leads to a mild to moderate elevation of liver transaminases in almost all cases, hepatic failure rarely dominates the clinical picture in adults. We present a case of dengue haemorrhagic fever in a young adult, leading to the rare complication of acute liver failure. He was managed with supportive care and discharged after 5 days. At follow-up after 1 week, he had complete recovery and no residual symptoms.